If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5x = 8x + 4 Combine like terms: 3x + -5x = -2x -2x = 8x + 4 Reorder the terms: -2x = 4 + 8x Solving -2x = 4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2x + -8x = 4 + 8x + -8x Combine like terms: -2x + -8x = -10x -10x = 4 + 8x + -8x Combine like terms: 8x + -8x = 0 -10x = 4 + 0 -10x = 4 Divide each side by '-10'. x = -0.4 Simplifying x = -0.4
| (W-6)(W-6)=25 | | 52=-4(-1+4x)+4x | | 5x+2y=148 | | x/1.15=0.4 | | 40-12= | | 60=4(3a+3) | | 8-2x=21 | | 4t-12= | | 2a(a+3)(8a-3)=0 | | 2t^3+8t^2+3=0 | | 3x+16=60 | | 10+2p=-2(2p+4) | | 10+2p=2(2p+4) | | -6(x-4)-(7x+1)=7 | | 42-2y=32 | | y=-1/6(-6/1)-3 | | 12x+4x-8=22x-22 | | 2=-1/6x+3 | | 51=3(4v+1) | | 1/4y=6 | | X-2X^4=0 | | x^2+2x-3=7 | | 7d-1=90 | | (z-3)(2z+10)(z-1)= | | 4(3x-1.6)=9x-6.4 | | 26=5x^2+7x+2 | | 4.2x-51=2.6x+5 | | y-8.8=8 | | 24/x | | 7(x-9.4)=2.1 | | 2x+27=45 | | 26=(2x+1)(3x+2) |